If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8sin(2x) + 5 = 0 Remove parenthesis around (2x) 8ins * 2x + 5 = 0 Reorder the terms for easier multiplication: 8 * 2ins * x + 5 = 0 Multiply 8 * 2 16ins * x + 5 = 0 Multiply ins * x 16insx + 5 = 0 Reorder the terms: 5 + 16insx = 0 Solving 5 + 16insx = 0 Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 16insx = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 16insx = 0 + -5 16insx = 0 + -5 Combine like terms: 0 + -5 = -5 16insx = -5 Divide each side by '16nsx'. i = -0.3125n-1s-1x-1 Simplifying i = -0.3125n-1s-1x-1
| 20=5(3+x) | | 21x-x^2=0 | | 4x+33=2x+15 | | 3*Ix-4I=10 | | X=-112+8 | | 2a-3b+4c=21 | | 2x+1=2x-9 | | X+16=8(x-12) | | 25-7x=-66 | | 3x-8=77 | | h=-16t^2-10+20 | | 5x+6=3x-20 | | (x^4)-(15x^2)+(10x)+(24)=0 | | 3(x-5)-4=55 | | 12x=(x^2)+(36) | | 0.5+0.34= | | (x^4)-(15x^2)+(10x)+24=0 | | 2(2y+4y)= | | x^4+2x^3+3x^2+4x+5=0 | | 7(x-20)-4x=10 | | 5x+47=7x-7 | | -4(2x-3)=11 | | 8[2(c+4)-(3c-9)]=c-24 | | 4p-6=2(2p-6) | | x^6-1+4x^3=0 | | 11+2x=x | | 4(y-2)=2(5-y) | | 2(x+10)+5x=83 | | 75-9y=5(-4+2x) | | 4(5x-10)=3(2x+1) | | -4x^2+3=11 | | 3(2y-4)=4y+6 |